If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = p + 6 Reorder the terms: 9 = 6 + p Solving 9 = 6 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. 9 + -1p = 6 + p + -1p Combine like terms: p + -1p = 0 9 + -1p = 6 + 0 9 + -1p = 6 Add '-9' to each side of the equation. 9 + -9 + -1p = 6 + -9 Combine like terms: 9 + -9 = 0 0 + -1p = 6 + -9 -1p = 6 + -9 Combine like terms: 6 + -9 = -3 -1p = -3 Divide each side by '-1'. p = 3 Simplifying p = 3
| 17*y=51 | | 7=y*6 | | 32t=128 | | 5z^2+20z=0 | | t-3=12 | | 20/y=4 | | x/2+(x-1)2=0.9 | | x(b-5)+s(b-5)=0 | | 24+2z-z^2=0 | | 7x-7+3x=38 | | 36c^2+49t^2-84ct=0 | | 3(4-2w)=18 | | 2/x+2/(x-1)=0.9 | | y=1/2*8-3 | | 21=-5x+46 | | 85x+y-10xy=58 | | -8x-5y=-1 | | 25s^2-60sf+36f^2=0 | | 81y^2-144=0 | | 2x-5y=-28 | | z/5+3z/2=7 | | 5(c-4)=6(c-8) | | -4y-10=2y+14 | | z=-x^2+6y^2-6x+12y+10 | | x^3-7x^2+7x-15=0 | | -8=-5(-4)+b | | 128b^3+54=0 | | 16+17-14+1-5-6= | | 7a(12)= | | (x-1)(x^2+10x+100)= | | 36b^2-121f^2=0 | | -25+(a)-8+3= |